Analisis Efektivitas Motion graphic Sebagai Media Informasi Company profile Polibatam Press Menggunakan Epic Model - Supardianto, Supardianto; Octaviany, Wanda Dwi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2023)
Polibatam Press, a business unit under the Batam State Polytechnic, which was founded in 2017, focuses on publishing books and scientific works. Even though it currently uses a website for publishing and social media for promotion, Polibatam Press does not yet have a company profile that can be easily distributed via various social media platforms. This research aims to develop a company profile video in the form of motion graphics to improve Polibatam Press branding. In the design process, the Villamil-Molina method was used, and its effectiveness was analyzed using the EPIC model. The research results showed that alpha testing was 4.23, which means